The Analysis of Occupational Health and Safety at the Muhammadiyah Lamongan Hospital - Eko Ari Bowo; Laely Ufiz Tsani Sugiyana; Nadiya Istighfaara; Maharani Nusara Ardhi; Irsyad Yudisianto; Burhanuddin Hilmi Muhammad (Darul Yasin Al Sys, 2025)
Hospitals, as complex healthcare institutions, present considerable occupational health and safety (OHS) risks due to the interplay of multiple stakeholders, technologies, and hazardous materials. Effective OHS management is essential to safeguard the well-being of workers, patients, and visitors. This study examines the implementation of OHS practices in the Inpatient Unit of Muhammadiyah Lamongan Hospital, utilizing a descriptive qualitative approach. Data were collected through in-depth interviews with three key informants: the Head of the Hospital’s OHS Department (K3RS) and a maintenance staff member (IPSRS officer). The findings indicate that Muhammadiyah Lamongan Hospital has implemented OHS measures in alignment with national standards, specifically the Regulation of the Minister of Health of the Republic of Indonesia No. 66 of 2016. Key practices include the provision of safety signs and personal protective equipment (PPE), safe handling and management of hazardous and toxic materials (B3), maintenance of medical infrastructure, and implementation of fire prevention and control systems. Emergency and disaster preparedness is supported by a structured response plan encompassing hazard identification, team organization, protective systems, and life-saving equipment. Despite these strengths, the study recommends several improvements: increasing the frequency of emergency drills and simulations, conducting routine OHS audits and evaluations, enhancing documentation practices, integrating advanced technologies into OHS systems, and promoting active staff participation to foster a robust safety culture. These efforts are essential to further strengthen OHS effectiveness and ensure a safer, healthier hospital environment.